(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Broadly researching the concept of early consciousness in psychology, this concept expands the scope of creative thinking between knowledge, skill acquisition, and interpretation of the concept of consciousness in controversial conversations among students.